Penertiban Kawasan Taman Nasional Bukit Tiga Puluh di Kabupaten Indragiri Hulu: Penelitian - Andika Utarini; Harapan Tua RFS (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Bukit Tiga Puluh National Park as a protected forest in Indragiri Hulu Regency is not spared from these illegal activities. Therefore, it is very necessary government management such as DLHK, police and other agencies authorized in curbing the protected forest. Research methods with descriptive qualitative approaches, located in Indragiri Hulu. Data collection techniques are carried out with a derivative, interview with 3 informants, and observations. Data analysis is expanded with reduction, display, and data verification. The results showed that the control process in the TNBT area with managerial processes based on George R. Terry’s theory where there were 4 variables namely planning, organizing, coordinating, and supervising. In DLHK planning an inventory and mapping, which is the work plan of the next managerial variable. In the process of controlling there are also obstacles, namely: 1) Lack of community legal awareness, 2) There are problems in the inauguration of the TNBT forest area boundaries.